Securing sustainable development through green economy in Uzbekistan - Rakhmonov Bekzod Sharibjon (Euro Asian Journal Publishing, 2024)
Uzbekistan's impressive economic growth over recent decades has come at a significant environmental cost, making the country one of the most greenhouse gas (GHG) emissions-intensive economies globally. This paper explores Uzbekistan's journey toward sustainable development and green growth, examining the challenges posed by its current economic practices and the initiatives undertaken to address them. The concept of green growth is presented as an evolution of sustainable development, emphasizing economic growth derived from environmental sustainability. Key areas of focus include energy reform, renewable energy deployment, and resilience to climate change. The paper also highlights the support from international development partners and the strategies for a low-carbon future.
Keywords: sustainable development; green growth; greenhouse gas emissions